THE EFFECT OF TAXES, INCENTIVES FOR ELIMINATION OF FINES AND EXEMPTION OF OWNERSHIP DUTIES ON THE LEVEL OF REGIONAL TAX REVENUE OF WEST JAVA PROVINCE DURING THE COVID-19 PANDEMIC - Asep Effendi (SEAN Institute, 2022)
During the CoVD-19 epidemic, this study will examine the impact of local tax relief (PKB) and motor vehicle transfer fees (BBNKB) provided under the Triple Profit Plus Program. The EViews-12 application was used to analyze panel data for this descriptive and verification research technique., a secondary data source for local taxes at the Bapenda of West Java Province during the Triple Profit Plus Program in 2021, with a population of 170 using the Cluster Random Sampling technique, and 95 Samsat offices as samples. During the Covid-19 Pandemic, West Java Province motor vehicle tax circumstances, incentives for the eradication of motor vehicle tax fines, free transfer of motorized vehicles, and regional tax revenues are in good shape, with regional tax revenues increasing. The positive correlation between local taxes and test scores is heavily influenced by a wide range of independent variables. The results of simultanous and partial tests of motor vehicle taxes, incentives for the elimination of motor vehicle tax fines, and free transfer of motorized vehicles have a significant impact on the direction of a good relationship with local tax revenues.